A atividade orientadora de ensino como organizadora do trabalho docente em Matemática: a experiência do clube de matemática na formação de professores dos anos iniciais - Borowsky, Halana Garcez (2013)
This study aims to search for training process of teachers in a group that organizes math teaching activities in a shared manner to the elementary school early years. Our theoretical assumptions are based on the Historical and Cultural Theory, Activity Theory and Guiding Educational Theory, which enable us to think of the teacher's action as an intentional activity and part of the teaching development. This research is being held in the context of the Mathematics Club (CluMat), from developing a teaching activity about Geometry. The data collection arises from reflective sessions (Ibiapina, 2008) with the participating teachers. These sessions were designed to lead teachers to focus their attention on the mathematics teaching organization for the early years and reflect on concepts and pedagogical practices. For data analysis, we make use of the movements that have being done by some researchers, taking as reference for data analysis in educational research, the concept of Isolated Caraça Bento de Jesus (1989). We list, therefore, three isolates we consider constituents of CluMat teachers training dynamic, which are: the mathematical knowledge, sharing actions and methodological resources. These elements, although isolated, are interdependent in the training movement, contributing to the CluMat be a special environment of teacher education and providing qualitative changes in the mathematics teaching organization for the elementary school early years. The results indicate that such changes are made possible in the collectivity, through shared activity (Rubtsov, 1996), and from the intention of the teacher - being materialized into a solid theoretical and methodological proposal. Thus, we demonstrate qualitative changes in the way of conceiving math and organizing the math teaching in the early years of the CluMat teachers, mostly from the appropriation of geometrical knowledge, the collective experiences and exchange experiences, as well as overcoming earlier conceptions in relation to mathematics education.